Концепція поля та капіталу П. Бурдьє в поясненні феномена маргінальності - Бутиліна, О. В.; Butylina, O. V.; ORCID: http://orcid.org/0000-0002-3943-4098 (Вісник Харківського національного університету внутрішніх справ. - 2014. - № 3 (66). - С. 232-240, 2014)
Для визначення соціальних суб’єктів, яким найбільше притаманні ознаки маргінальності, застосовано методику моделювання соціального простору. В основу моделі багатомірного соціального простору покладено положення концепції поля та капіталу П. Бурдьє. Зроблено аналіз соціального простору. Виявлено найбільш маргіналізовані групи суспільства. Ґрунтуючись на теоретичних тезах П. Бурдьє, визначено та проаналізовано три види маргінальності: економічну, політичну та культурну.

The phenomenon of marginality as an objective and natural phenomenon of social life is investigated. The topicality of this study has been stipulated for the need to improve the theoretical and methodological explanations for structures and types of marginality. The main objective of the article is the analysis of Pierre Bourdieu’s concept of field and capital to study and explain the phenomenon of marginality, to define and characterize political, economic and cultural marginality. To define social subjects, whom characteristic features of marginality are the most inherent, one uses in the article the technique of modelling of social space. Principles of Pierre Bourdieu’s concept of field and capital form the basis of the model of multidimensional social space. Social space is reproduced in the interaction between people and has several lines of differentiation. Each of the fields stratified in this space has its own structure. The study offers to conditionally define two structural elements of the field: «a core», being the set of individuals, who are carriers of the bulk of scarce capital, and «a periphery», in which people are settled, who are severely restricted in using the appropriate capital or even do not own it at all. According to the presented theoretical model of social space, the marginality is considered by the author as a set of positions of an individual or a social group, which are far from the conventional «core» of the field. The present model has allowed identifying and describing some of the most marginalized segments of the society. Based on theoretical theses of Pierre Bourdieu the author of the article has identified and analysed three types of marginality: economic, political and cultural. The author concludes that the further study of the phenomenon of marginality will help to identify behaviour strategies of marginal men, which reflect their response to displacement in the periphery of a given field.

Для определения социальных субъектов, которым наиболее присущи признаки маргинальности, использована методика моделирования социального пространства. В основе модели многомерного социального пространства использованы положения концепции поля и капитала П. Бурдье. Проведён анализ социального пространства. Выявлены наиболее маргинализированные группы общества. Основываясь на теоретических тезисах П. Бурдье, выделены и проанализированы три вида маргинальности: экономическую, политическую и культурную.
Концепция поля и капитала П. Бурдье в объяснении феномена маргинальности
P. Bourdieu’s concept of field and capital to explain the phenomenon of marginality
Бутиліна, О. В. Концепція поля та капіталу П. Бурдьє в поясненні феномена маргінальності / О. В. Бутиліна // Вісник Харківського національного університету внутрішніх справ. - 2014. - № 3 (66). - С. 232-240.
Keywords: Соціологія. Соціальна робота. Sociology. Social Work. Социология. Социальная работа; Наукові публікації. Scientific publications. Научные публикации; маргінальність; поле; капітал; економічна маргінальність; політична маргінальність; культурна маргінальність; концепція поля та капіталу П. Бурдьє; Бурдьє П.; концепция поля и капитала П. Бурдье; Бурдье П.; маргинальность; экономическая маргинальность; политическая маргинальность; культурная маргинальность; Bourdieu’s concept of field and capital; marginality; field; capital; economical marginality; political marginality; cultural marginality; Bourdieu Pierre